Iminodiacetic acid-functionalized gold nanoparticles for optical sensing of myoglobin via Cu2+ coordination - Zhang, Xianfeng (Langmuir : the ACS journal of surfaces and colloids, 2011)
A novel gold nanoparticle (AuNP)-based optical sensing system has been developed for the detection of myoglobin (Mb), which is of significant importance for early disease diagnosis. Two thiol molecules containing an iminodiacetic acid moiety (IDA) were synthesized. This detection is based on the Mb-induced aggregation of IDA-functionalized AuNPs resulting from the structures of Mb sandwiched between the functionalized AuNPs via Cu(2+) bridges in the coordination interactions of IDA-Cu(2+)-histidine residues available on the Mb surface, which was confirmed by UV-vis spectroscopy, transmission electron microscopy, dynamic light scattering, and matrix-assisted laser desorption/ionization time-of-flight mass spectrometry. The induction aggregation resulted in a red shift in plasmon resonance band of the AuNPs concomitant with a change in solution color from red to purple. The qualitative and quantitative detections of Mb can be achieved by colorimetric observations and UV-vis spectral measurements, respectively. The selectivity of protein assay with the functionalized AuNPs was further investigated, and it is found that the optical sensing of histidine-rich proteins is closely related to number and distribution of surface histidine residues as well as size of proteins